Three blind mice: oxford literacy web - Gaines, Keith; Doyle, Mandy (Oxford University Press China, 1999)
Presents a literacy programme meant to guide schools through the primary years, to meet the requirements of the National Literacy Strategy, National Curriculum in England and Wales, English Language 5-14 in Scotland, and Common Curriculum in Northern Ireland. This pack offers wordless stories to develop book knowledge and practise language skills.